Brain Morphological Alterations Are Detected in Early‐Stage Parkinson's Disease with MRI Morphometry. Issue 6 (17th August 2020) - Fu, Tong; Klietz, Martin; Nösel, Patrick; Wegner, Florian; Schrader, Christoph; Höglinger, Günter U.; Dadak, Mete; Mahmoudi, Nima; Lanfermann, Heinrich; Ding, Xiao‐Qi
ABSTRACT: BACKGROUND AND PURPOSE: To detect brain morphological alterations in patients with early Parkinson's disease (PD) by using magnetic resonance imaging (MRI) morphometry under radiological diagnostic conditions. METHODS: T1‐weighted brain images of 18 early PD patients and 18 age‐sex‐matched healthy controls (HCs) were analyzed with free software Computational Anatomy Toolbox (CAT12). Regional cortical thickness (rCTh) in 68 atlas‐defined regions‐of‐interest (ROIs) and subcortical gray matter volume (SGMV) in 14 atlas‐defined ROIs were determined and compared between patients and HCs by paired comparison using both ROI‐wise and voxel‐wise analyses. False‐discovery rate (FDR) was used multiple comparison correction. Possible correlations between brain morphological changes in patients and clinical observations were also analyzed. RESULTS: Comparing to the HCs, the ROI‐wise analysis revealed rCTh thinning significantly in left medial orbitofrontal ( P = .001), by trend ( P < .05 but not significant after FDR correction) in four other ROIs located in frontal and temporal lobes, and a volume decreasing trend in left pallidum of the PD patients, while the voxel‐wise analysis revealed one cluster with rCTh thinning trend located between left insula and superior temporal region of the patients. In addition, the patients showed more distinct rCTh thinning in ipsilateral hemisphere and SGMV deceasing trends in contralateral hemisphere in respect of the symptom‐onset body side. CONCLUSION: Brain morphological alterations in early PD patients are evident despite of their inconspicuous findings in standard MRI. Quantitative morphological measurements with CAT12 may be an applicable add‐on tool for clinical diagnosis of early PD. These results have to be verified in future studies with larger patient samples.